Role of Interleukin-1 Family Members and Signaling Pathways in KSHV Pathogenesis - Barrett, Lindsey; Chen, Jungang; Dai, Lu; Plaisance-Bonstaff, Karlie; Del Valle, Luis; Qin, Zhiqiang (Frontiers in Cellular and Infection Microbiology, 2020)
Kaposi’s sarcoma-associated herpesvirus (KSHV) represents the etiological agent for several human malignancies, including Kaposi’s sarcoma (KS), primary effusion lymphoma (PEL), and multicentric Castleman’s disease (MCD), which are mostly seen in immunocompromised patients. In fact, KSHV has developed many strategies to hijack host immune response, including the regulation of inflammatory cytokine production. Interleukin-1 (IL-1) family represents a major mediator for inflammation and plays an important role in both innate and adaptive immunity. Furthermore, a broadening list of diseases has revealed the pathologic role of IL-1 mediated inflammation. In the current mini-review, we have summarized recent findings about how this oncogenic virus is able to manipulate the activities of IL-1 signaling pathway to facilitate disease progression. We also discuss the therapeutic potential of IL-1 blockade against KSHV-related diseases and several unsolved questions in this interesting field.